Introduction to English for Immigrant Children through The One Day One Culture Program at SB Hulu Kelang - Nurfaikah, Nurfaikah; Naimah, Naimah; Jafar, Muhammad; Syarifuddin, Syarifuddin; Said, DIan Riani (Syntax Literate, 2024)
This article discusses the "One Day One Culture" program at Sanggar Belajar Hulu Kelang, which aims to introduce English to immigrant children through a cultural approach. By integrating English language learning and local culture, especially Javanese and Sundanese culture, the program helps children adapt to their new environment while enriching their learning experience. Through interactive activities, such as vocabulary introduction and batik art, children learn English in a fun way. The teaching method includes an introduction to Javanese and Sundanese, as well as Kawung and Mega Mendung batik, which strengthens their understanding of Indonesian cultural heritage. The program shows significant potential in supporting the social integration of immigrant children and increasing their love for local culture, as well as building confidence in communicating. As a result, this activity not only introduces language, but also creates multicultural awareness among students.